Analisis Perbandingan Metode Grover dan Altman dalam Memprediksi Financial Distress pada Perusahaan Sub Sektor Hotel, Restoran, dan Pariwisata yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2020-2023 - Basaria Francisca Maharani; Anissa Yuniar Larasati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the comparison between the Grover and Altman methods in predicting financial distress in hotel, restaurant, and tourism subsector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023. The background of this research is the significant impact of the COVID-19 pandemic on the financial performance of the tourism sector, which caused many companies to experience losses. This study employs a quantitative approach with a comparative method. The research sample consists of 16 companies selected using purposive sampling based on specific criteria, resulting in 64 observations. The analysis was conducted using the Altman Z-Score and Grover models, followed by descriptive statistics, normality testing, comparative testing, as well as accuracy and type error calculations. The results indicate differences in prediction outcomes between the two models. The Grover model tends to produce more conservative results compared to the Altman model. The accuracy rate and type error analysis show that the Grover model is more accurate in predicting financial distress in this research sample. This study is expected to serve as a reference for investors, companies, and academics in evaluating potential bankruptcy in the future.